A High-Throughput Method for the Analysis of Larval Developmental Phenotypes in Caenorhabditis elegans. Issue 2 (20th August 2015) - Olmedo, María; Geibel, Mirjam; Artal-Sanz, Marta; Merrow, Martha
Abstract: Caenorhabditis elegans postembryonic development consists of four discrete larval stages separated by molts. Typically, the speed of progression through these larval stages is investigated by visual inspection of the molting process. Here, we describe an automated method to monitor the timing of these discrete phases of C. elegans maturation, from the first larval stage through adulthood, using bioluminescence. The method was validated with a lin-42 mutant strain that shows delayed development relative to wild-type animals and with a daf-2 mutant that shows an extended second larval stage. This new method is inherently high-throughput and will finally allow dissecting the molecular machinery governing the speed of the developmental clock, which has so far been hampered by the lack of a method suitable for genetic screens.